2015
DOI: 10.5897/ajar2015.9771
|View full text |Cite
|
Sign up to set email alerts
|

Yield and oil content of peanut (var. TMV-7) and sunflower (var. Co-2) applied with bio-stimulant AQUASAP manufactured from seaweed

Abstract: The effect of bio-stimulant AQUASAP manufactured from seaweed Kappaphycus alvarezii (Rhodophyta) farmed in Indian water on the yield and oil content of peanut and sunflower was studied under field condition. The AQUASAP at 5% foliar application promoted the vegetative growth, yield and oil content in both peanut and sunflower significantly. Compared to control the yield of seed in peanut increased by 31.69% with 14.27% more oil content similarly on sunflower the increase in seed yield and oil content were 51.5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…It also contains plant growth hormones that enhance yield (Latique et al 2013). Application of seaweed extract stimulates growth and yield and increases the tolerance of plants to environmental stress (Pramanick et al 2013), improves germination of maize seeds by 10-19%, promotes shoot and root growth by 30-68% (Matysiak et al 2011), increases the resistance of herbaceous plants to drought (Zhang and Ervin 2004), promotes vegetative growth, yield and oil content of peanuts (31.69%, 14.27%) and sunflower (31.69%, 14.27%), respectively (Karthikeyan and Shanmugam 2015). In addition, spraying plants with seaweed extract improves growth, yield and tuber quality of potatoes in terms of their nitrogen, total soluble solids and protein contents (Haider et al 2012), increases root growth, nutrient absorption, stem thickness and growth (Jensen 2004), ameliorates effect of salt stress on bean seeds because of the presence of growth hormones, nutrients and other important phytochemical compounds (Latique et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…It also contains plant growth hormones that enhance yield (Latique et al 2013). Application of seaweed extract stimulates growth and yield and increases the tolerance of plants to environmental stress (Pramanick et al 2013), improves germination of maize seeds by 10-19%, promotes shoot and root growth by 30-68% (Matysiak et al 2011), increases the resistance of herbaceous plants to drought (Zhang and Ervin 2004), promotes vegetative growth, yield and oil content of peanuts (31.69%, 14.27%) and sunflower (31.69%, 14.27%), respectively (Karthikeyan and Shanmugam 2015). In addition, spraying plants with seaweed extract improves growth, yield and tuber quality of potatoes in terms of their nitrogen, total soluble solids and protein contents (Haider et al 2012), increases root growth, nutrient absorption, stem thickness and growth (Jensen 2004), ameliorates effect of salt stress on bean seeds because of the presence of growth hormones, nutrients and other important phytochemical compounds (Latique et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…As for the salinity factor, the stress caused by excess ions compromises the photosynthetic system and reduces transpiration, gas exchange, and stomatal conductance, harming crop yield and justifying the reduction in achene yield as a result of increased salinity levels (Pan et al, 2021). Karthikeyan & Shanmugam (2015), in a study on applying algae-based biostimulants to sunflower crops, noted a 51.03% increase in crop yield compared to the control treatment. Similarly, Sîrbu et al (2022) found an 8% increase in sunflower yield when treated with algae-based fertilizer.…”
Section: Resultsmentioning
confidence: 99%
“…There is still little information on the agricultural use of algae extract in sunflower cultivation; however, in previous studies, some researchers have obtained increases in the production and yield of this crop. Sírbu et al (2022) found an 8% increase in sunflower yield when treated with algaebased fertilizer; Karthikeyan & Shanmugam (2015) observed a 51.03% increase in crop yield, while Suganthi & Sujatha (2014) found a 14% increase in the 1,000-achene weight of sunflower treated with algae compared to the control.…”
Section: Introductionmentioning
confidence: 99%
“…(Kumawat, P., & Dawson 2022) [19] . The Aquasap (Brand name of AquAgri for bio-stimulant of seaweed K. alvarezii) significantly increased the seed yield and oil content of peanut by 31.69% and 14.27%, similarly on sunflower the increase in seed yield and oil content was 51.50 and 15.77% respectively (Karthikeyan, K., & Shanmugam, M. (2015) [15] . Kiruthika et al, (2022) reported that application of 75% RDF + poultry manure @ 10 t ha -1 through soil application along with foliar application of 15% seaweed extract at 30 and 60 DAS and harvest stages recorded maximum soil nutrient availability [17] .…”
Section: Introductionmentioning
confidence: 99%